A comprehensive review of everolimus clinical reports: a new mammalian target of rapamycin inhibitor - Gurk-Turner, Cheryle; Manitpisitkul, Wana; Cooper, Matthew (Transplantation, 2012)
As new immunosuppressive agents are introduced to the market, clinicians are faced with the daunting task of sifting through the published literature to decide the value that the agent will add to their own practice. We often must extrapolate information provided through study in other solid-organ transplantation populations than our specific area of interest as we interpret the results and outcomes. With these challenges in mind, this compilation of published work for the newest mammalian target of rapamycin inhibitor everolimus (Certican; Novartis Pharmaceuticals, Hanover, NJ) (Zortress; Novartis Pharmaceuticals, Basel, Switzerland) is intended to provide a concise but thorough presentation of available literature so that the reader who may be unfamiliar with the agent can make their own judgment. Both Ovid and PubMed search engines were queried with a particular focus on high-impact articles noted in the Web of Science or Citation Index. Work described solely in abstract or case report form was excluded, as well as meta-analyses or those that were editorial or commentary in nature. Included were publications presented using the English language that described adult human subjects who received a heart, lung, kidney, or liver allograft. The goal of this strategy was to allow for the inclusion of pertinent literature in an unbiased fashion. Tables are provided that outline trial specific information, leaving a discussion of major outcomes to the text of the review.